Physiological demand and pacing strategy during the new combined event in elite pentathletes - Le Meur, Y.; Dorel, S.; Baup, Y.; Guyomarch, J. P.; Roudaut, C.; Hausswirth, C. (European Journal of Applied Physiology, 2012)
To evaluate the physiological demands and effects of different pacing strategies on performance during the new combined event (CE) of the modern pentathlon (consisting of three pistol shooting sessions interspersed by three 1-km running legs). Nine elite pentathletes realised five tests; a free-paced CE during an international competition; an incremental running test to determine VO²max and its related velocity (vVO²max) and three experimental time-trial CE, where the pacing strategy was manipulated (CEref, CE100%, CE105%). CEref reproduced the international competition strategy with a 170-m fast running start within the first 2 km. CE100% and CE 105% imposed a constant strategy over km-1 and km-2 with a velocity of 100 and 105% of the mean speed adopted over the same sections during the international competition, respectively. Km-3 was always self-paced. The subjects ran CEref at 99 ± 4% of vVO²max and reached 100 ± 5, 100 ± 7, 99 ± 8% of VO²max at the end of kilometres 1, 2 and 3, respectively (VO²max: 72 ± 6 mL O² min-1 kg-1), with a peak blood lactate concentration of 13.6 ± 1.5 mmol L -1. No significant differences in overall performance were found between the pacing conditions (753 ± 30, 770 ± 39, 768 ± 27 s for CEref,CE100% and CE105%, respectively, p = 0.63), but all of the shooting performance parameters were only stable in CEref. Completion of CE by elite pentathletes elicits a maximal aerobic contribution coupled with a high glycolytic supply. Manipulating the mean running speed over km-1 and km-2 had strong influence on the overall pacing strategy and induced minor differences in shooting performance, but it did not affect overall performance.